Evaluation of Serum Homocysteine and Folate Levels in Patients with Ischemic Stroke: A Biochemical Correlation Study - Rahman, Obaid Ur; Ali, Anwar; Ahmed, Ayaz; Khalilullah, Khalilullah; Shuaib, Faiza; Badar, Adnan (Journal of Neonatal Surgery, 2025)
Background: According to the American Heart Association, strokes are a leading cause of disability and death due to biochemical elements such as homocysteine. And folates are becoming increasingly critical given their impact on thrombosis and vascular damage. It is easy to recognize that, in rough and clinical settings, efficient early monitoring, accurate prediction, and better process management are going to be substantially determined by estimates of the elements above. Objectives: To evaluate serum homocysteine and folate levels in patients with ischemic stroke and examine their associations with stroke characteristics, demographic variables, clinical risk factors, and relevant biochemical parameters. Methodology: this study conducted at department of Biochemistry Saidu Medical College Saidu Sharif Swat from Jan 2025 to June 2025.100 adults who were CT/MRI-confirmed ischemic stroke patients within 72 hours of admission were included in the cross-sectional study. Serum levels of homocysteine and Folate were measured using a chemiluminescence enzyme immunoassay. The NIHSS was used to assess stroke severity. Demographic and clinical information were documented. The data were analyzed using SPSS version 24.0, including t-tests, Pearson’s correlation, and Chi-square tests, with a p-value of ≤ 0.05. Results: 100 patients mean age was 59.8 ± 10.6 years. Elevated homocysteine levels were observed in 62% of patients, while low folate levels were detected in 38%. A significant inverse correlation was found between homocysteine and folate levels (r = –0.41, p = 0.002). Higher homocysteine levels were significantly associated with moderate-to-severe stroke on NIHSS (p = 0.01). Folate deficiency showed a significant association with older age and hypertension (p = 0.03). No significant association was found with gender (p = 0.27). Conclusion: The study shows there are significant correlations between ischemic strokes and an increased prevalence of hyperhomocysteinemia and folate deficiency. Additionally, there's an increased risk of vascular morbidity. The inverse biochemical relationship supports the association of folate deficiency with hyperhomocysteinemia. Regular assessment of such indicators may assist in initial risk classification and in the provision of optimal nutritional and preventive measures to support better outcomes for the cerebrovascular system